HUBUNGAN ANTARA KARAKTERISTIK PERSONAL DENGAN SIKAP LANSIA TERHADAP PELAYANAN DI PANTI WREDHA DHARMA BHAKTI SURAKARTA - Ratih Dwi Lestari; Kartinah Kartinah (Universitas Muhammadiyah Surakarta, 2009)
Improvement of number of elderly in Indonesia affects at improvement of number of dwellers panti wredha. Position elderly to panti wredha itself all kinds. There is various factors relating to with position of acceptance receiving of elderly at panti wredha. One of them is is responder characteristic covering age, gender, and level of education. This research aim to know the relation of age, gender, and level of education to position elderly to the service in Panti Wredha Dharma Bhakti Surakarta. This research is descriptive research of correlative with approach of cross sectional. Research sample is 46 responders with technique simple random sampling. Data processing technique applies correlation analytical technique Rank Spearman. Conclusion from this research is: ( 1) most of elderly are woman, ( 2) most of lansia is having age 60 - 79 years, ( 3) level of education of elderly most of doesn’t have school experience, and (4) there are no relationship betwen of gender, age, and level of education to position lansia to the service in Panti Wredha Dharma Bhakti Surakarta.